The Competitiveness of Indonesian Agricultural Products in G-20 Market - Endang Pudji Astuti; Rita Nurmalina; Amzul Rifin (Agro Ekonomi, 2022)
Membership in the G-20 forum is both a threat and an opportunity for Indonesian agricultural commodities. Indonesia must be able to take advantage of this great opportunity to increase international trade activities, especially exports. Although the G-20 market is a potential market, Indonesia faces challenges because it is considered not ready to compete and threatened to become a market for other countries. In 2020, Indonesia's agricultural exports (HS 01-24) are in ninth place compared to its competitors in G-20 market. In order to increase the export share, the purpose of this study is to analyze the development of exports  from Indonesia to the G20 market and the competitiveness of agricultural products. The analyzes used are descriptive analysis, Revealed Comparative Advantage (RCA), and Dynamic Revealed Comparative Advantage (DRCA). The results showed that 63.25% of the five selected agricultural export commodities had comparative competitiveness in the G-20 market. From the trend of increasing exports, several countries that become non-traditional markets have the potential as a market diversification destination, including Saudi Arabia, Mexico, Turkey, and Argentina. DRCA analysis shows that the dynamics of the G-20 market are quite large, and some of them are experiencing a decline. The strategy to increase exports to the G-20 market is to maintain the competitiveness of commodities in the rising star quadrant, as well as increase the competitiveness of commodities that are in the lagging opportunity and lost opportunity quadrant due to high global demand for these commodities.